Perception of College Professors Regarding Healthcare Facilities - Sushil Kumar (International Journal of Engineering and Management Research, 2023)
According to the economic survey of Haryana healthcare department of Haryana is continually improving its infrastructure, human resource, tools, instruments, machinery and medicines etc. Health Department of Haryana is covering healthcare requirements of entire population that comprises infant, children, adolescent, and female during pregnancy etc . At present Haryana healthcare sector is having the coverage with 57 hospitals, 112 community healthcare centers, 485 primary health centers, 2630 sub centers, 7 Trauma centers, 37 urban and rural dispensaries, 90 urban RCH centers and 473 delivery huts. Moreover 11 polyclinics, 4 dispensaries, 11 urban centers have also been on track. As per literature and other Government statistics there is a huge gap as to what is required and what is available in healthcare industry. Which reveals that lot needs to be done in present state of healthcare facility as it’s not quite satisfactory. Thus in the present paper it was decided to work on Perception of College Professors Regarding Healthcare facilities. The total paper is divided in five sections i.e. Backdrop, review of literature, research methodology, data Analysis and interpretation followed by conclusions.